Social support needs of first-time parents in the early-postpartum period: A qualitative study - Schobinger, Elisabeth; Vanetti, Mélanie; Ramelet, Anne-Sylvie; Horsch, Antje (Frontiers in Psychiatry, 2022)
Background: The early postpartum period is a critical time for first-time parents as they adapt to their new role. Perceived lack of social support is a risk factor for developing mental health problems. Insufficient or inappropriate professional support for both parents has been reported by many studies. Social support that appropriately meets parents’ needs is an important protective factor for parents’ wellbeing; however, little is known about the social support needs of both first-time parents. Aims and objectives: To describe both first-time parents’ formal social support needs in the early postpartum period. Method: Individual semi-structured interviews were conducted with first-time parents recruited on the postpartum ward of a Swiss university hospital. Thematic analysis was used to identify themes and sub-themes. Results: Fifteen mothers and eleven fathers were interviewed. Twelve themes were identified. Mothers’ themes were “experiencing postpartum changes”, “creation of a family unit”, “self-esteem”, “emotional needs”, and “the postpartum stay”. Fathers’ themes were “to be included in care procedures on the postpartum ward”, “to be reassured”, “to anticipate their postpartum stay” and “to consider their need as non-priority”. Parental shared needs were: “to care for their newborn”, and “returning home”. Conclusion: Mothers’ and fathers’ needs differed. Mothers needed more emotional support than fathers and fathers considered themselves as the main support for their partner. Fathers wanted to be integrated in the care of their newborn.